Functional Relations of Artistic Ideology and Leadership of Didin Sirojuddin at Lemka Sukabumi, West Java - Hadi Alhail; Muhammad Ihsanul Fikri; Muhammad Rafli Syakbani; Neni Trinovita; Raihan Luthfi Rahman; Adek Cerah Kurnia Azis; Kurniawansyah Kurniawansyah; Khodijah Khodijah (Gorga : Jurnal Seni Rupa, 2025)
This study aims to analyze the functional relationship of art ideology and the leadership of Didin Sirojuddin AR in the management of the Islamic Calligraphy Islamic Boarding School LEMKA Sukabumi, West Java. This study departs from the phenomenon of a gap in academic research on art specialists in pesantren, even though the work of LEMKA and Didin Sirojuddin is very significant in producing national and international calligraphers. The research uses a qualitative method with a case study design. Data were collected through observation, open interviews, documentation, and archival studies, then analyzed using Spradley's model in four stages (domain, taxonomy, component, and event structure). The results of the study show that the art ideology embraced by Didin Sirojuddin is rooted in Islamism with the fundamental values of monotheism and taqwa. This ideology is internalized in the curriculum, work ethic, and work traditions at LEMKA. Calligraphy is seen as worship, da'wah, and a cultural medium with five primary forms of works: manuscripts, mushaf decoration, decoration, contemporary, and digital. In terms of leadership, Didin Sirojuddin applies a participatory style with a visionary and democratic orientation. This style is characterized by the team's active involvement in decision-making, a collaborative space, and persuasive communication that encourages the loyalty and creativity of students and alumni. The relationship between ideology and leadership has proven to be a key factor in the formation of effective pesantren management and a conducive learning climate. The synergy between the two results in high-quality work, competitive achievements, and a wide alumni network. This study concludes that the success of LEMKA is a combination of a strong religious ideology and transformative kiai leadership, while offering an integrative model for the development of Islamic arts education.